Arte e loucura em um estudo de caso no CAPS II em Toledo-Pr - Pierazo, Isabela Olsen (2019)
The theme of this research is the relationship between art and madness, considering the implementation of complementary and integrative practices focused on mental health, especially the artistic practices performed within institutional spaces such as the Psychosocial Care Centers - CAPS, in the process of constitution of the reform. psychiatric care in Brazil. To this end, this dissertation problematizes, initially, the struggles for reform by pointing out the demands, themes and involved subjects engaged in the process, in order to achieve the main objective of giving visibility and understanding the narratives of madness related to the participation of users in workshops. art, through a case study, inside a CAPS II of the city of Toledo / PR. The research techniques used to fulfill the proposed objective were: participant observation, data and document analysis, semi-structured interviews with local professionals and users and photography. All techniques were used in order to grasp the narratives in a more meaningful way, especially that of users who attend artherapy workshops. Experiences that can be great allies in the work of political and cultural transformation of the imaginary around madness.